STUDY OF USAGE OF MOBILE LEARNING AMONG THE PRE-SERVICE TEACHERS OF RANGAREDDY DISTRICT - Mr. Sayam Deepathi (EPRA International Journal of Research and Development (IJRD), 2022)
Mobile learning allows educational institutions to expand their educational services beyond the boundaries of their classrooms right into the reading rooms of their learners. the present investigation is taken up with aim to assess the usage of mobile learning by pre-service teachers in Ranga Reddy district and to assess the usage of mobile learning by pre-service teachers with respect to their gender, management and methodology. This investigation is employed by descriptive survey method on sample size of 200 drawn through purposive method of sampling. A researcher developed tool was employed to gather data to study. This tool consists of 15 statements, where respondents are instructed to opt with one or all options method of responding. Data analysis is done by using simple descriptive statistics and analyzed in two sections whereas Section-A deals with analysis of data (overall) and Section-B deals with analysis of data with respect to their gender, management and methodology. The major findings include, most of the pre-service teachers are using chrome app (90%) on their mobile tools and for academic purpose they are using what’s app (87%),for presentation MS Power point (88.5%) ,for taking pictures (70%) for making videos (60%) doing assignments (56%) and also using for personal use (70.5%).they are using their university website occasionally to check the result (66%) and for exam syllabus (60.5%).